The Role of Machine Learning in Predicting and Understanding Inflation Dynamics: Insights from the COVID-19 Pandemic - Kanaparthi, Vijaya (2024 3rd International Conference on Artificial Intelligence For Internet of Things (AIIoT), 2024)
Inflation, or the increase in prices of goods and services, has become a significant issue during the Covid-19 pandemic. I explore diverse Machine Learning techniques to forecast inflation in the USA, prioritizing understanding over mere replication, dissecting method mechanics and key factors during periods of rapid price escalation.The findings indicate that ML models are indeed helpful in predicting inflation in the USA. Specifically, the more advanced non-linear models like random forest and ada boost perform better, especially during periods of high inflation. During high inflation, traditional factors like price trends and the Phillips curve still have explanatory power, but inflation itself tends to drive prices more prominently due to the unique dynamics of such periods.